(untitled) (Nóema, 2015)
A question. If the patient knows what he is doing, and he knows why he is doing so, why should we interpret it instead of asking him why? Bion. This is another mystery. Why cannot we transfer it directly from himself to himself? Why is an external person necessary? Why are nonhuman beingslike an earthworm? Why should we need a partner? Why cannot we have a sexual life with ourselves without any other annoying problems? Why cannot we have a direct relationship with ourselves without the interventionof some kind of mental or physical“obstetrician”? It seems that we need to “rebound” on another person and to have something that could reflect back what we say before any comprehension (Bion, 1984b, p. 59). In order to know who I am, I need to ask it to you. Therefore my essence is outside me. You, the others, are “my” secret. The eccentric nature of the human animalis studied through a reflectionon the work of the psychoanalyst Wilfred Bion. With a last question: if I am you, the I – in itself – does not exist. Thus, is it an impostor? Is there a way to be an Iwhich is not fictitious?